Influence Of Local Government Integrity On The APBD And Its Implications For Development - Indra Jaya; Sri Mulatsih; Mohammad Iqbal Irfany (SEAN Institute, 2024)
Regional development involves the utilization of available resources to significantly improve the welfare of the community, including in financial aspects. One of the benchmarks for successful regional development can be measured by the Gross Regional Domestic Product (PDRB) data of each region. PDRB can show the trend of economic growth from year to year, provide information on the economic resource capabilities of a region, and more. In measuring regional development based on PDRB, the Regional Revenue and Expenditure Budget (APBD) also plays a key role in the planning and implementation of development programs. In government institutions with high integrity, public employees are expected to perform their duties with professionalism, avoid conflicts of interest, and report any ethical or legal violations they encounter. The aim of this study is to analyze the influence of the level of local government integrity on APBD management and its implications for the quality of regional development in Indonesia. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS) for APBD and PDRB data, and from the Corruption Prevention Network (JAGA) website for SPI data. The data used includes PDRB, SPI, and APBD for cities and regencies in Indonesia in 2022. The results of the study show that higher local government integrity can improve the management of their APBD; conversely, lower integrity can decrease it. The influence of local government integrity on APBD is relatively small, as the success of APBD management is also influenced by other factors beyond the scope of this study. However, in essence, APBD management requires a high commitment to integrity from the local government, as the APBD management process can be exploited as a means for certain funds' disbursement. Integrity in government institutions can reduce the risk of corruption. Higher integrity is predicted to improve APBD. Thus, local government integrity plays a key role in ensuring the success and sustainability of regional finances and provides a broad positive impact on development and community welfare